CRITICAL ANALYSIS OF MAQĀṢIDĪ TAFSĪR ON DISASTER MITIGATION IN THE STORY OF PROPHET LŪṬ: AN EXAMINATION OF THE INTERPRETATION OF Q.S. AL-ḤIJR: 61-74 - Tri Faizah Anggraini (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir)
This research is motivated by the complexity of disasters that occur in the latest era but trigger disaster mitigation responses that tend to be passive. In the Qur'an, indications of disaster mitigation are presented through the narrative Lūṭ story. However, the story of Lūṭ is often read with reference to the centrality of the sexuality of the Sodomites, so that aspects of disaster mitigation are often marginalized. The interpretation of Q.S al-Ḥijr (15):61-74 also tends to be read textually so that it does not touch the maqȃṣid aspect behind the verse. On these problems, this study seeks to answer, how the critical analysis of maqāṣidi tafsīr on Disaster Mitigation in Q.S al-Ḥijr (15): 61-74. This question intends to explore what the maqȃṣid behind the presence of disaster mitigation orders in the story of the prophet Lūṭ. The results showed that the maqȃṣid aspects of the verse are hifdz al-dīn, hifdz al-nafs, hifdz al-nasl, hifdz al-'aql and hifdz al-mȃl. At the same time, the maqȃṣid dimension is the value of humanity represented in the humanism of Lūṭ who helped his people and the value of freedom of choice for the people of Lūṭ to follow Lūṭ's da'wah by leaving the abominable act so as to obtain salvation. By using the analysis of maqāṣidi tafsīr, an interpretation is obtained that goes beyond the internal aspects of the text so that the purpose behind the presentation of the story of Lūṭ in this verse is increasingly revealed. This makes maqāṣidi tafsīr bring up a unique perspective of novelty so that the principles of disaster risk management can be deduced for related institutions.